Sigorta şirketlerinin prim ve kar payı değerlendirilmesine matematiksel yaklaşım - Doğan, Çiğdem (My University, 2006)
Sigorta işletmeleri yarattıkları fonlarla ekonomiye büyük ölçüde ivme kazandırmaktadır. Sigortalıların gönüllü tasarruflarıyla toplanan primler sigorta işletmeleri tarafından yönetilerek, mali kesime aktarılır ve rasyonel alanlarda yatırımlara yönlendirilirler. Bu çalışma ile ekonomilerin gelişmişlik göstergesi olan sigorta sektörünün Türkiye’deki konumu, prim ve kar paylarının değerlendirilmesi ve fonların yönetilmesi konularına değinilerek anlatılmaya çalışılmıştır. Türkiye ekonomisinde sigorta sektörünün ağırlığı fazla hissedilmemesine karşın, son yıllarda sağlanan ekonomik istikrar ve yapılan düzenlemelerle, sigorta sektörü hızlı bir şekilde hak ettiği konuma ulaşmaya başlamıştır. Büyük ölçüde fon birikimi sağlayan sigorta sektörüne verilen önemin artmasıyla beraber, ekonomide olumlu gelişmelerin gözleneceği bir gerçektir.

The insurance companies have been highly accelarating the economy by the funds which they create. The annuaties which are aggregated by the voluntary savings of the insureds are managed by the insurance companies, conveyed to the fiscal part and directed to the investments in rational areas. In this study, the position of the insurance sector -which is one of the basic evidences of economical growth in nations- in Turkey has been attempted to be described by examining the subjects of the utilization of profits and annuaties and the fund management. In spite of the fact that the significance of the insurance sector in Turkish economy is not perceived enough, the insurance sector has started dramatically reaching to the status which it actually deserves by the help of some arrangements and the economical stability that has been established recently. It is obvious to see that positive changes in the economy will be observed by the increase in the importance paid to the insurance sector which provides huge amounts of fund accumulation.
Keywords: Sigorta Şirketleri; Sigortacılık_Kar Payı